Determinants of the low labor force participation among people at preretirement age - Jurek, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Population aging decreases amount of aggregate labor force. Nowadays it is seen as a one of the most important socio-economical issues, that endanger sustainability of welfare state. There are two reasons of that decrease. First, is shrinking productive-age population, and second - raising share of older cohorts, that has relatively lower activity rate.The article is about the situation on the labor market of people at pre-retirement age. Low activity rate of that group is a well known problem, but its causes are still insufficiently researched. Aim of the article is to diagnose the determinants of low economic activity among people at preretirement age. The statement of the crucial factors, that excludes this group from the labor market, was identified basing on the broad literature studies.There are two kinds of forces, that limit activity rate among elders. First of them "push out" from the labour market. That is: negative attitudes and discrimination because of old age, public over-intervention in the field of anti-discrimination programs, economics of corporate employment policy and also labour market policy aimed at deactivation of older workers. The second is "pull into" inactivity. The point is, that institutional settings in the field of social security system discourage lengthening professional activity.